Paragonimus westermani as a cause of Löeffler's syndrome. (2022) - Furuya, Satoshi; Fukui, Sayato; Maekawa, Yoichiro; Aoki, Nozomi; Inui, Akihiro; Naito, Toshio
Abstract: In 1936, Löeffler first recognized the association between a distinctive form of severe heart failure and marked eosinophilia. Most cases are caused by either parasitic infections or drugs; however, no cause has been identified in one-third of the patients [1]. This report presents a rare case of Löeffler's syndrome caused by the parasite Paragonimus westermani.